Day 1 Mon, May 01, 2017 2017
DOI: 10.4043/27666-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production Chemistry: Exposing Hidden Treasures or Generating Complications?

Abstract: According to a recent study, more than 50 percent of the world's energy currently comes from oil and natural gas. So how does Production Chemistry discipline play a role in this? Can we use the discipline to enhance or accelerate production? And what happens if we get it wrong? Will it have a detrimental impact on production? The Production Chemistry threats to business are getting more challenging and frequent, reflecting the changing complexity of our Project and Operations portfolio (deeper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Saturation ratio dictates the solid precipitation kinetics as the chemical driving force to promote precipitation. As a matter of fact, in oilfield operations, mineral scale threat is commonly characterized by the calculated saturation ratio values of different solids. , Saturation ratio is calculated as: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saturation ratio dictates the solid precipitation kinetics as the chemical driving force to promote precipitation. As a matter of fact, in oilfield operations, mineral scale threat is commonly characterized by the calculated saturation ratio values of different solids. , Saturation ratio is calculated as: …”
Section: Resultsmentioning
confidence: 99%
“…Various types of scale inhibitor chemicals including environmentally friendly inhibitors have been formulated and produced in the past several decades to control scale threat at different operating conditions. However, the first line of defense in oilfield scale control relies on the correct assessment of scale threat, which is still an ongoing challenge in the oil and gas industry. This requires the knowledge and deep technical insights of the thermodynamics and kinetics aspects of the scale deposition process given the operating conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…This is because it is substantially difficult and extraordinarily more expensive to remediate scale damage in downhole formation or bottom of the well-compared to further upstream places such as processing facilities. It has been reported that the cost to remediate scale damage in a subsea well can be as high as tens of millions USD (Zhang et al, 2017a). In addition, the operational risks associated with downhole scale remediation and removal are considerably more than that at processing facilities (Cosultchi et al, 2002;Hajirezaie et al, 2019).…”
Section: Chemical Inhibition and Delivery Methodsmentioning
confidence: 99%
“…Decades ago when hydrocarbons were primarily produced from conventional onshore fields, flow-assurance-related operational issues were less pronounced. However, with the significant developments in offshore deepwater and shale fields in the past two decades, the associated flow assurance challenges greatly threaten oilfield operational integrity and safety (Mackay et al, 2005;Vazquez et al, 2016;Vankeuren et al, 2017;Zhang et al, 2017a;Chang et al, 2019). Common oilfield flow assurance threats include gas hydrate blockage, mineral scale formation, asphaltene deposition, pipe corrosion, and wax (paraffin) formation (Gao et al, 2006;Kelland, 2006Kelland, , 2011Kelland, , 2014Frenier and Ziauddin, 2008;Zerpa et al, 2011;Wang et al, 2018;Qasim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Properly handling these flow assurance challenges become especially critical for offshore deepwater operations where the operating conditions of high reservoir pressure, low seawater temperature and high salinity can considerably exacerbate the flow assurance issues (Gao et al, 2006;Wang et al, 2018). Laboratory studies and field observations suggest that flow assurance related operational issues can result in a substantially elevated operational risk as well as a significant financial loss (Gao et al, 2006;Mackay et al, 2005;Zhang et al, 2017). Mineral scale (hereafter referred to as "scale") is the hard crystalline inorganic precipitate formed from the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%